Pola Perilaku Konsumsi Generasi Millenial Terhadap Produk Fashion Perspektif Monzer Kahf : Studi Kasus Mahasiswi Universitas Airlangga - Arlinda Nidia Corinna; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study examines how consumption patterns of millennial generation towards fashion products based on Monzer Kahf's perspective, especially female students from Airlangga University. The research method uses descriptive case study method. Data collection in this study was carried out by in-depth interview method and the subjects of the study were asked the questions immediately. The analysis technique carried out in this study is by reducing data, presenting data both through the results of interviews and observations of researchers towards the informants, then proceed with drawing conclusions. The results of the study show that the principles of Islamic consumption from Monzer Kahf's perspective have been applied by Airlangga University students as a pattern of consumption behavior towards fashion products. Millennials in Indonesia, especially university students, are principled by consumption in accordance with Islamic teachings by promoting consumption rationalism, consumption balance, Islamic goods and consumption ethics.Keywords: Consumption, Islamic consumption, Millenials, Fashion Product, Rationalism, Consumption Balance, Islamic GoodsREFERENCES Al Arif, M. Nur Rianto & Amalia, Euis. 2010. Teori Mikroekonomi: Suatu Perbandingan Ekonomi Islam dan Ekonomi Konvensional. Jakarta: Kencana.Rahardja, P & Manurung, M. 2008. Teori Ekonomi Makro. Edisi 4. Jakarta: Fakultas Ekonomi Universitas Indonesia. Dagun, Save M. (1992). Pengantar Filsafat Ekonomi. Jakarta: Rineka Cipta.Engel, James F. dkk. Perilaku Konsumen. (Edisi keenam Jilid 1). (Penerjemah: F.X Budiyanto). Jakarta: Binapura Aksara.Walter Nicholson, Microeconomic Theory; Basic, Principles and Extensions (Ohio: Thomson Corporation, 2005), 69-70.Suparmoko, Pengantar Ekonomika Mikro .Yogyakarta: BPFE-YOGYAKARTA. 1998Nugroho J. Setiadi, Perilaku Konsumen Konsep dan Implikasi untuk Strategi dan Penelitian Pemasaran . Jakarta: Kencana. 2005M. Nur Rianto al-Arif dan Euis Amalia, Teori Mikroekonomi; Suatu Perbandingan Ekonomi Islam dan Ekonomi Konvensional . Jakarta: Kencana.  2010 Suprayitno, Eko. Ekonomi Mikro Prespektif Islam. Malang : Sukses Offset. 2008Sudarsono, Heri. Konsep Ekonomi Islam. Yogyakarta : Ekonisia. 2007Muhammad Nejatullah Siddiqi, The Economic Enterprise, diterjemah oleh Anas Sidik, Kegiatan Ekonomi dalam Islam (Cet. ke-2; Jakarta: Bumi Aksara, 1996), h. 95.Yusuf Qardhawi, Dawr al-Qiyam wa al-Akhlāq fī al-Iqtiṣad al-Islāmī, diterjemah oleh Zainal Arifin dan Dahlia Husim, Norma dan Etika Ekonomi Islam, (Cet. ke-4; Jakarta: Gema Insani Press, 1422 H./2001 M.), h. 352.Boudrillard, Jean L. 2011. Masyarakat Konsumsi, terjemahan Wahyunto. Bantul: Kreasi  Wacana. Jauhar ,Ahmad Al-Mursi Husain. Maqashid Syariah, Jakarta:Amzah,2010.Ahmad Qorib, Ushul Fikih 2, (Jakarta: PT. Nimas Multima, 1997), Cet, II), hlm. 170.M.Umer Chapra. Masa Depan Ilmu Ekonomi Sebuah Tinjauan Islam.(Tazkia Cendekia. 2001), Hlm 102.Karim , Adiwarman Azwar. Ekonomi Mikro Islam. Jakarta : IITI . 2004.Kahf , Monzer. Ekonomi Islam : Telaah Analitik Terhadap Fungsi dan Sistem Ekonomi Islam. Terjemahan Machnul Husein. Yogyakarta : Pustaka Pelajar. 1995.Siddiqi, Muhammad Nejatullah. Kegiatan Ekonomi Dalam Islam. Terj. Anas Sidik. Jakarta : PT Bumi Aksara. 2004.Sukirno, Sadono. Pengantar Teori Ekonomi Mikro. Jakarta : Raja grafindo Persada. 2002Khan, Muhammad Fahim. Essays In Islamic Economics. United Kingdom : The Islamic Foundation. 1995.Moleong, Lexy.J. Metode Penelitian Kualitatif, (edisi : revisi). Bandung : PT Remaja Rosda Karya. 2006.Sugiyono.  Metode Penelitian Kuantitatif Kualitatif dan R&D.  Bandung: CV Alfabeta. 2010 Arikunto, Suharsimi. 2005. Dasar-Dasar Evaluasi Pendidikan. Jakarta: Bumi Aksara. Patilima, Hamid. 2007. Metode Penelitian Kualitatif. Jakarta: Alfabeta.Miles, MattHew B.Miles dan A. Michael Huberman. 2007. Analisis Data Kualitatif Buku Sumber tentang Metode-Metode Baru. Terjemahan Tjetjep Rohendi Rohisi. Jakarta: Universitas Indonesia. Harsono. 2008. Model-Model Pengelolaan Perguruan Tinggi. Yogyakarta: Pustaka Pelajar. Sutama. 2010. Metode Penelitian Pendidikan. Cetakan pertama. Surakarta: Fairuz Media. Yin, Robert K, 2008, Studi Kasus (Desain Dan Metode), (Case Study Research Design and Methods”) diterjemahkan oleh Drs. M. Djauzi Mudzakir, MA, PT.Raja Grafindo Persada,Jakarta